Topical application of imatinib mesylate suppresses vitamin D3 analog‐induced dermatitis in Balb/c mice. Issue 4 (11th December 2022) - Seshimo, Harutaka; Egusa, Chizu; Maeda, Tatsuo; Numata, Takafumi; Okubo, Yukari; Harada, Kazutoshi; Ito, Tomonobu
Abstract: Atopic dermatitis (AD) is an allergic disease mediated by Th2 cells. In AD, externally stimulated keratinocytes release inflammatory cytokines, such as IL‐33 and TSLP. Inflammatory cells infiltrate skin tissue and increase vascular permeability. Therefore, we hypothesized that imatinib mesylate (IMT), which suppresses vascular permeability, may be a candidate therapeutic agent for AD. A vitamin D3 analog (MC903) was administered daily to both ears of Balb/c mice to create a murine AD model to which IMT was applied. The skin lesions were evaluated histopathologically and by immunostaining. Cytokine expression in the skin was assessed by using real‐time polymerase chain reaction (PCR) and immunostaining and was investigated using Evans Blue to determine whether IMT suppressed vascular permeability due to histamine. The suppressive effect of TNF‐α/IL‐4‐induced TSLP expression in primary mouse keratinocytes (MKCs) treated with IMT was then investigated. Tslp gene and protein expression in the lesion was measured using real‐time PCR and ELISA. The activation of signal transduction was analysed by western blotting. Topical application of IMT significantly reduced ear thickness, Evans blue leakage, and scratch onset. IMT suppressed the number of infiltrating cells (CD4+ T cells, eosinophils, and basophils), and the expression of IL‐13, IL‐33, and TSLP in a MC903‐induced, murine AD model and inhibited TNF‐α/IL‐4‐induced TSLP expression via downregulation of ERK phosphorylation in MKCs. IMT reduced the skin symptoms in a MC903‐induced, murine AD model, suggesting that it may have potential as a new treatment for AD.